Prevalence Of Dental Caries Among Smokers And Non Smokers Visiting A Private Dental Institution - A Retrospective Study - ABITHA S, TASLEEM; SANTHANAM, ARCHANA; MANI, GEO (The journal of contemporary issues in business and government, 2021)
Introduction:Dental caries is one of the most prevalent oral diseases. It is the primary focus of dental health prevention as it is one the most prevalent chronic diseases . Smoking is a public health problem that harms one’s general and oral well-being. In smokers, Nicotine would promote the attachment of streptococcus mutans to the dental surface, and further increases the incidence and severity of dental caries. In non smokers, a frequent high intake of fermentable carbohydrates, especially sucrose, has been known to be associated with caries initiation and development. The aim of the present study was to find out the association of dental caries between smokers and nonsmokers. Materials and Methods :During the period from June 2019 to March 2020, we reviewed the case record of 86000 patients out of which a total of 1000 smokers and 1000 non smokers between the age group of 18-40 years with dental caries were selected for this study. A customized examination form was used to collect the data and a special table for data collection was prepared. The data collected was classified according to no of caries affected teeth, no of missing and filled teeth. DMFT index was also calculated. Dependent variables were dental caries and Independent variables are smokers and non smokers. Data were analysed using descriptive statistics and chi square test was done to determine the association between the caries and smokers and non smokers. P value less than or equal to 0.05 was considered as statistically significant. Results :Among the 1000 smokers and non smokers, around 97% of the patients were male. The prevalence of dental caries was more among the age group of 31-40 years in smokers (44%) and 18-25 years in non-smokers (38.7%). Average number of teeth affected by caries was 4-6 caries among smokers and non smokers with p=0.015 and number of filled teeth, missing teeth was found to be more in smokers than non smokers. DMFT value of smokers was found to be more than non smokers with p value = 0.559 statistically not significant. Conclusion :From the present study, it can be concluded that smokers have more number of dental caries compared to non smokers.